Concept of Principles of International Economic Law - I. S. Chabaeva (Московский журнал международного права, 2010)
This article relates to disclosure of the concept of principles of international economic law. Domestic and foreign authors’ approaches on how to treat principles of international economic law as legal regimes and standards, as well as some arguments regarding the impossibility of such treatment are presented there. A list of principles of the international economic law, which is not exhaustive, as well as international documents, which set forth or specify the principles under the question, are given. The question of legal availability in the treaties of the category of “economic sovereignty” became the subject matter under analysis. Current positions on recognition of a legal binding or, in contrast, non-binding nature of these documents and, as a result, statements related to the «soft law», which is indicated by different terms in doctrine, as well as the question of whether the principles of international economic law consolidated in these documents to be considered as mandatory, are reflected. The question relating to the forms of legal existence of the principles of international economic law with regards to external forms of expression, i.e. international treaty and international custom is perused.